Aggregate Prevalence of Chemosensory and Sinonasal Dysfunction in SARS-CoV-2 and Related Coronaviruses. (July 2020) - Lehrich, Brandon M.; Goshtasbi, Khodayar; Raad, Richard A.; Ganti, Ashwin; Papagiannopoulos, Peter; Tajudeen, Bobby A.; Kuan, Edward C.
Much of the published literature regarding the novel coronavirus disease 2019 (COVID-19) constitutes lower respiratory system symptomatology, while there exists a paucity of data describing the complicated sequelae of the upper respiratory system, including chemosensory and/or sinonasal dysfunction. This study utilized the National Library of Medicine's PubMed/MEDLINE database to query for articles describing COVID-19, SARS-CoV-2, SARS-CoV-1, MERS-CoV, and other coronaviruses, with any mention of smell, taste, or other chemosensory or sinonasal dysfunction. Aggregate analysis demonstrated an incidence of 49.6% (n = 497 of 1002; 95% CI, 46.5%-52.7%), 47.9% (n = 480 of 1002; 95% CI, 44.8%-51.0%), and 17.9% (n = 880 of 4909; 95% CI, 16.9%-19.0%) for smell loss, taste loss, and smell or taste loss, respectively, in patients infected with SARS-CoV-2. Additionally, there were significantly higher incidences of runny nose/rhinorrhea/rhinitis and nasal congestion/obstruction/blockage in other coronaviruses as compared with SARS-CoV-2 ( P < .001). Understanding these less well-characterized symptoms may help develop measures for estimating early markers of disease prevalence and/or resolution. Level of evidence: 4.